PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KUALITAS LABA - Rilo M M, Ricky; Laksito, Herry (Diponegoro Journal of Accounting, 2017)
The aim of the research is to investigate the influence of audit committee characteristics on earnings quality. Independent variables on this research included size of audit committee, independence of audit committee, number of meetings of audit committee, and tenure of audit committee. While the dependent variable is earnings quality. This research also used 2 control variables included company size and company leverage.This research is a quantitative research using secondary data such as data in the annual report which are manually taken through official site of Bursa Efek Indonesia. Population of this research is the whole 136 manufacturing companies listed on Bursa Efek Indonesia constanly or successively along 2014 – 2016. Then 74 companies are selected to match the criteria. This research uses linear regression analysis method for hypothesis testing.The results showed that audit committee size and audit committee independence are have no effect on earnings quality. Number of meetings has positive effect on earnings quality, which frequently meetings can solve companies problems fastly. While audit committee tenure has negative effect on earnings quality, which someone who officiate in long time as a audit committee on a certain company knowing some opportunities in a company to doing earnings management practices.